The Role of Platelet-Rich Plasma in Enhancing Bone and Cartilage Healing - Liaqat Khan, Feroz Shah, Abdul Waheed, Ahsan Ul Haq, Adil Saidullah, Aman Ulhaq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Platelet-rich plasma (PRP) and other regeneration techniques are necessary to improve tissue repair since bone and cartilage lesions have a limited natural healing capability. Objective: This study aimed to evaluate the effectiveness of PRP in promoting bone and cartilage healing by assessing its impact on tissue regeneration, functional mobility, and pain reduction. Methodology: A prospective observational study was conducted from January 2021 to December 2022. The study included 208 patients undergoing PRP treatment, 104 of whom had bone fractures and 104 of whom had cartilage damage. A consistent centrifugation procedure was used to produce PRP, which was then injected intra-articularly or peri-lesionally. Clinical outcomes were evaluated using radiographic imaging, functional mobility scores (WOMAC for bone fractures, KOOS for cartilage injuries), and pain levels (VAS) at baseline and at follow-up visits at 3, 6, and 12 months. SPSS version 25 was used for the statistical analysis, and a p-value of less than 0.05 was deemed significant. Results: At one year, 81.73% of patients had cartilage regeneration and 89.42% had bone healing (callus development) (p=0.008). Better joint function was indicated by a substantial improvement in WOMAC and KOOS scores (p<0.001). Considerable pain alleviation was seen by the considerable reduction in VAS values (p<0.001). For bone fractures, the total clinical success rate was 83.65%, whereas for cartilage injuries, it was 78.85%. Conclusion: PRP dramatically improves bone and cartilage repair, increasing functional mobility and decreasing discomfort; nevertheless, further research is required to standardize its use for reliable results. Keywords: Platelet-rich plasma, bone healing, cartilage regeneration, regenerative medicine, orthopedic therapy.